International Human Rights Law and the Protection of the Elderly in Europe - Tonolo, Sara (Medicine, Law & Society, 2018)
The protection of the elderly is a fundamental topic within the international human rights law, strictly connected to the perceived centrality of a person with disabilities as subject of rights. Some problems may arise as much from the absence of a uniform definition of elderly people and of person with disabilities, as from the different national rules on this matter. In fact the rights of elderly people have not yet received the international legal attention they deserve. Many treaties refer to rights that are of particular interest to the elderly, but there is no comprehensive international instrument that adequately addresses the specific protections required for the elderly. Actually, standards that protect older people’s rights are scattered throughout various international and regional conventions. There is no doubt that the elderly are protected by human rights treaties, as is any member of society, however, in order to realistically guarantee equal enjoyment of those rights to older persons, states must do more than refrain from violating human rights of every member of society.Varstvo starejših je osrednja tema mednarodnega prava človekovih pravic, ki je strogo povezana z zaznavno centralnostjo invalidne osebe kot subjekta pravic. Problemi se lahko pojavijo zaradi pomanjkanja enotne definicije starejših in invalidov, kot tudi zaradi različnih nacionalnih pravil v zvezi s tem. Dejansko pravice starejših oseb še niso prejele mednarodne pravne pozornosti, ki si jo zaslužijo. Številne pogodbe se nanašajo na pravice, glede katerih imajo starejši poseben interes, vendar ni celovitega mednarodnega instrumenta, ki ustrezno obravnava posebno varstvo, ki ga potrebujejo starejši. Pravzaprav so standardi, ki ščitijo pravice starejših, razpršeni po različnih mednarodnih in regionalnih konvencijah. Ni dvoma, da so starejši zaščiteni s pogodbami o človekovih pravicah, kot je vsak član družbe, vendar pa morajo države, da bi dejansko zagotovile enako uživanje teh pravic starejšim osebam, storiti več kot le vzdržati se kršitev človekovih pravic vsakega člana družbe.